Metabarcoding and morphological analysis of diets of mesopelagic fishes in the NW Atlantic Slope Water - Bucklin, Ann; Batta-Lona, Paola G.; Questel, Jennifer M.; McMonagle, Helena; Wojcicki, Melissa; Llopiz, Joel K.; Glancy, Sarah; Caiger, Paul E.; Francolini, Rene; Govindarajan, Annette; Thorrold, Simon R.; Jech, Michael; et al. (Frontiers in Marine Science, 2024)
DNA metabarcoding and morphological taxonomic (microscopic) analysis of the gut contents was used to examine diet diversity of seven species of fishes collected from mesopelagic depths (200-1000 m) in the NW Atlantic Ocean Slope Water during Summer 2018 and 2019. Metabarcoding used two gene regions: V9 hypervariable region of nuclear 18S rRNA and mitochondrial cytochrome oxidase I (COI). V9 sequences were classified into 14 invertebrate prey groups, excluding fish due to predator swamping. Ecological network analysis was used to evaluate relative strengths of predator-prey linkages. Multivariate statistical analysis revealed consistently distinct diets of four fish species in 2018 and/or 2019: Argyropelecus aculeatus, Chauliodus sloani, Hygophum hygomii, and Sigmops elongatus. Three other species analyzed (Malacosteus niger, Nemichthys scolopaceus, and Scopelogadus beanii) showed more variability between sampling years. COI sequences were classified into eight invertebrate prey groups, within which prey species were detected and identified. Considering all predator species together, a total of 77 prey species were detected with a minimum of 1,000 COI sequences, including 22 copepods, 18 euphausiids, and 7 amphipods. Morphological prey counts were classified into seven taxonomic groups, including a gelatinous group comprised of soft-bodied organisms. The ocean twilight zone or is home to exceptional diversity and biomass of marine fish, which are key players in deep sea food webs. This study used integrative morphological-molecular analysis to provide new insights into trophic relationships and sources of productivity for mesopelagic fishes, including identification of key prey species, recognition of the importance of gelatinous prey, and characterization of differences in diet among fish predators in the NW Atlantic Slope Water.